Evaluation of motor development in children with learning disabilities - Josiane Medina-Papst; Inara Marques (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to determine whether children with learning disabilities present any impairment in the components of motor development. Thirty children (21 boys and 9 girls), aged 8 to 10 years, with learning difficulties in school were studied. The Motor Development Scale was used to evaluate the development of the children in terms of fine motor control, gross motor control, balance, body scheme, spatial organization, and temporal organization. A deficit in the development of the body scheme component was observed for all three age groups, as well as a delayed motor development in terms of balance and gross motor control. No significant differences in general motor age were observed between (age) groups. In conclusion, the children studied, especially older ones, presented motor deficits in most of the components evaluated. The inclusion of tasks that assist in the development of motor components, in addition to regular school tasks, is recommended to improve the process of learning in these children..